RATIONALE FOR THE USE OF METHODS OF MICROSCOPIC CRYSTALLOGRAPHY IN FRACTALS OF PROTEINS AND IRRIGATION FOR THE EARLY DIAGNOSIS, TREATMENT AND PREVENTION OF INFLAMMATORY PROCESSES IN THE ORAL CAVITY - Skrypnykov, P.M.; Khavalkina, L.M.; Korobeinikova, Y.L.; Korobeinikov, L.S.; Tymoshenko, Yu.V. (World of Medicine and Biology, 2020)
In dentistry, new methods of prevention and treatment of diseases caused by aggressive biofilm are constantly offered. If timely oral hygiene and preventive measures are ignored or underestimated, the impact of aggressive biofilm can be irreversible and cause changes in periodontal tissues. One of the key factors that worsen the general state of oral health is the presence of removable and fixed dentures in patients. This is because soft dental plaque forms much faster on the surface of implant. Today, one of the most effective and optimal methods used for the prevention and treatment of inflammatory processes in the oral cavity is irrigation. We examined a total of 90 people. The age of the patients ranged from 40–60 years. Of these, there were 40 men and 50 women. Analyzing the value of the protein fractals, namely the area, we assessed and confirmed the hygienic condition of the oral cavity in people with dental protheses. An application of the periodontal tissue irrigation method for fixed dental protheses leads to a decrease in the percentage of protein fractals area in the digital crystallography samples. The results are confirmed by statistical and clinical data.
Keywords: microscopic crystallography; irrigation; oral cavity; periodontium; metal-ceramic fixed dental prostheses